Recreational lands use in King Abdullah Economic City in Rabigh Governorate: A study in geographic services - Alamri, Sarraa Mushab (Journal of Humanities & Social Sciences, 2022)
The study deals with the use of recreational land in the economic city of King Abdullah, Rabag Province, which is one of the largest urban projects in Saudi Arabia and is designed with the latest urban concepts to be one of the most important recreational cities in Saudi Arabia in the 2030. The study aims to identify patterns of distribution of recreational land, and to determine the characteristics of recreational activities in the study area. To achieve these goals, the analytical descriptive methodology for collecting spatial and metadata data and facts on the topic of the study area’s recreational lands was adopted and then analysed and processed. The written method was used to present findings and conclusions. The study concluded by presenting the most important findings that 68% of the recreational land fell within the normative circle and the distribution direction takes the northeast direction. When establishing recreational sites, the study recommends that consideration be given to the fact that there is no random location identification.